Creatine Supplementation as an Adjunct to Exercise in Type 2 Diabetes: Effects on Muscle Metabolism and Glycemic Control – A Literature-Based Review - Modelewski, Patryk Marek; Jakub Białożyt; Wagner, Weronika; Dębniak, Anna; Twardy, Patryk; Gutarowicz, Maciej; Nieradka, Kaja; Klahs, Krystyna; Armatys, Michał; Muraszko-Kuźma , Maciej (Quality in Sport, 2026)
Introduction and aim of the study. This study aimed to evaluate the role of creatine supplementation, particularly in combination with physical activity, in the management of type 2 diabetes mellitus, with emphasis on muscle metabolism and glycemic control. Research materials and methods: A literature-based review was conducted using major scientific databases, including PubMed, Scopus, and Web of Science. The analysis included randomized controlled trials, systematic reviews, and mechanistic studies investigating creatine supplementation and its metabolic effects in diabetic and non-diabetic populations. Basic results: Creatine plays a central role in cellular energy metabolism through the phosphocreatine system. Evidence suggests that supplementation may enhance glucose uptake via increased GLUT-4 translocation, improve insulin sensitivity, and support skeletal muscle function. When combined with exercise, creatine may exert synergistic effects on glycemic control. However, available clinical evidence remains limited and heterogeneous. Conclusions: Creatine supplementation may be a promising adjunct strategy in the management of type 2 diabetes, particularly when combined with regular physical activity. Further high-quality clinical trials are required to establish clear clinical recommendations.